2015
DOI: 10.1093/femspd/ftv058
|View full text |Cite
|
Sign up to set email alerts
|

Francisella tularensistype B ΔdsbAmutant protects against type A strain and induces strong inflammatory cytokine and Th1-like antibody responsein vivo

Abstract: Francisella tularensis subspecies tularensis is a highly virulent intracellular bacterial pathogen, causing the disease tularemia. However, a safe and effective vaccine for routine application against F. tularensis has not yet been developed. We have recently constructed the deletion mutants for the DsbA homolog protein (ΔdsbA/FSC200) and a hypothetical protein IglH (ΔiglH/FSC200) in the type B F. tularensis subsp. holarctica FSC200 strain, which exerted different protection capacity against parental virulent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Here, we employ ⌬dsbA as a reference. The mutant is attenuated and provides protection in vivo (33). However, the production of IL-1␤ in infected DCs suggests that ⌬dsbA probably reaches the host cytosol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we employ ⌬dsbA as a reference. The mutant is attenuated and provides protection in vivo (33). However, the production of IL-1␤ in infected DCs suggests that ⌬dsbA probably reaches the host cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…Francisella Mutant Lacking dsbA Gene May Serve As An Avirulent Control to WT Strain in BMDCs-The identification of DC signaling pathways regulated in response to Francisella virulent behavior could be facilitated by the confrontation of results with experiments in which attenuated strain was used as a control. Francisella strains lacking dsbA gene (⌬dsbA) are attenuated in vivo and provide the protection against subsequent challenge by parental strain (31)(32)(33). The engagement of adaptive immunity suggests that ⌬dsbA would represent suitable alternative to WT in terms of DC response.…”
Section: Francisella Induces Two Waves Of Protein Phosphorylation In mentioning
confidence: 99%
“…Various mutant strains of subsp. holarctica , mainly in the background of LVS, have been developed, including mutants that have a lesion in a pathway or gene involved in nutrient metabolism ( purMCD ), response to oxidant stress ( sodB, emrA1 ), the heat shock response ( clpB ), putative capsular synthesis ( capB ), membrane integrity (FTL_0325, FTL_0057, wbtA, wzy ), transcription ( mglA) , disulfide bond formation ( dsbA ), and other functions (Bakshi et al, 2006 , 2008 ; Pechous et al, 2006 , 2008 ; Meibom et al, 2008 ; Sebastian et al, 2009 ; Jia et al, 2010 , 2013 ; Kim et al, 2012 ; Barrigan et al, 2013 ; Golovliov et al, 2013 ; Mahawar et al, 2013 ; Straskova et al, 2015 ; Suresh et al, 2015 ). Some of these strains have demonstrated significant attenuation by the intranasal (i.n.)…”
Section: Live Attenuated Subsp Holarctica Vaccinementioning
confidence: 99%
“…This has been accompanied by a substantial increase in publications on development of tularemia vaccines, mostly on live attenuated vaccine candidates, including defined mutants of F. tularensis subsp. holarctica (Bakshi et al, 2006 , 2008 ; Pechous et al, 2006 , 2008 ; Li et al, 2007 ; Sebastian et al, 2007 , 2009 ; Meibom et al, 2008 ; Sammons-Jackson et al, 2008 ; Santiago et al, 2009 ; Jia et al, 2010 ; Zarrella et al, 2011 ; Kim et al, 2012 ; Schmitt et al, 2012 ; Barrigan et al, 2013 ; Golovliov et al, 2013 ; Mahawar et al, 2013 ; Straskova et al, 2015 ; Suresh et al, 2015 ), F. novicida (Pammit et al, 2006 ; Tempel et al, 2006 ; Mohapatra et al, 2007 ; Quarry et al, 2007 ; Kanistanon et al, 2008 ; West et al, 2008 ; Cong et al, 2009 ; Sanapala et al, 2012 ; Signarovitz et al, 2012 ; Chu et al, 2014 ; Cunningham et al, 2014 ), and subsp. tularensis (Twine et al, 2005 , 2012 ; Qin et al, 2008 , 2009 ; Conlan et al, 2010 ; Michell et al, 2010 ; Shen et al, 2010 ; Ireland et al, 2011 ; Rockx-Brouwer et al, 2012 ; Reed et al, 2014 ; Santiago et al, 2015 ), but also on live attenuated heterologous vaccines expressing F. tularensis proteins (Jia et al, 2009 ; Kaur et al, 2012 ; Banik et al, 2015 ) and recombinant LVS vaccines expressing F. tularensis proteins (Jia et al, 2013 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on selection criteria we further focused on gene encoding cytosolic glycolytic enzyme, glyceraldehyde-3-phosphate dehydrogenase, whose level was significantly elevated in the dsbA mutant strain. This protein was previously shown to be immunoreactive, (Havlasová et al, 2005 ; Chandler et al, 2015 ; Straskova et al, 2015 ), and identified by proteomic analyses in fractions of enriched membrane proteins (Pávková et al, 2005 ) and CFPs (Konecna et al, 2010 ). These previous findings were in accordance with an increasing number of studies demonstrating additional activities of GAPDH not related to its primary metabolic function in both eukaryotic and prokaryotic cells.…”
Section: Discussionmentioning
confidence: 96%